2020
DOI: 10.1016/j.eclinm.2020.100347
|View full text |Cite
|
Sign up to set email alerts
|

First successful field evaluation of new, one-minute haemozoin-based malaria diagnostic device

Abstract: Background: Early and accurate diagnosis of malaria is critical to the success of malaria elimination. However, the current mainstay of malaria diagnosis in the field, such as light microscopy and rapid diagnostic tests (RDTs), have limitations due to low parasite density or mutation in diagnostic markers. Methods: We evaluated an inexpensive, robust, rapid, malaria diagnostic device, called Gazelle, that employs magneto-optical detection to identify haemozoin crystals (Hz) produced by all species of human mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 25 publications
0
58
0
2
Order By: Relevance
“…Kumar et al. observed that the sensitivity and specificity of Gazelle™ was 98 and 97 % compared to light microscopy, 82 and 99 % to PCR, and 78 and 99 % to RDT, respectively, in a predominantly P. falciparum endemic area [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al. observed that the sensitivity and specificity of Gazelle™ was 98 and 97 % compared to light microscopy, 82 and 99 % to PCR, and 78 and 99 % to RDT, respectively, in a predominantly P. falciparum endemic area [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… (a) Malaria 1 NAAT LAMP kelch 13 1 c/r <20 min -- ( Malpartida-Cardenas et al, 2019 ) 2. Gazelle Magneto-optical detection haemozoin crystals 50 parasites/mL ∼1 min Yes ( Kumar et al, 2020 ) 3. MCFA Chemiluminescence-based ELISA PfHRP2 8 ng/mL -- Yes ( Ghosh et al, 2020 ) (b) Dengue fever 4.…”
Section: Iomt-assisted Poc Biosensing For Infectious Diseasesmentioning
confidence: 99%
“…Besides this, instrument-free detection can be easily performed in rural areas to avoid expensive molecular biology equipment e.g., paper-based microfluidics ( Reboud et al, 2019 ). Further, Kumar et al conducted successful field evaluation of battery-operated magneto-optical malaria diagnostic device ( Kumar et al, 2020 ). In comparison to detection of P. falciparum histidine rich protein-2 (Pfhrp2), this device was based on detection of hemozoin (by-product of HB) due to its prevalent nature in resistant parasites.…”
Section: Iomt-assisted Poc Biosensing For Infectious Diseasesmentioning
confidence: 99%
“…Microscopic diagnosis using blood smears is considered the gold standard, not only for the identification of Plasmodium species, but also for the quantification of parasite load in blood. However, detection can be limited in those cases with low parasite loads, in addition to having other drawbacks such as the need for an optical microscope, clean glass slides, immersion oil, reagents for staining, and most importantly, a skilled microscopist [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, immunological techniques and the development of various RDTs have allowed quick diagnosis in the field, although with rather high economic costs [6]. However, RDTs have limitations in those cases with low parasite density or due to mutations in diagnostic markers [5]. Considering the decrease of the prevalence in many areas and the low detection limits of microscopy and RDTs, there is the need for the development of effective diagnostic strategies for field application [7].…”
Section: Introductionmentioning
confidence: 99%